The necessity of analysing cities in a comprehensive way - Peter M.J. Pol (European Regional Science Association (ERSA), 2002)
City planners can have an enormous impact on human actions. They make important choices which influence how people for decades or even centuries live and travel in urban areas. The realised ideas of urban planners have large influence on social interrelations, the use of transport modes, the quality of life, the economic potential of urban districts, etc.. City developers often develop urban Idealtypen, theoretical models of urban configurations, deliberately overstressing some aspects of reality, while neglecting others. Therefore, creating more or less rational distortions of reality. The Idealtypen are used to provide insight in urban configurations to be striven for. Examples of urban Idealtypen are the Garden City, the Radiant City and the Broadacre City. What kind of urban Idealtypen are developed in the last centuries, and what influence did they have on urban reality? How where such Idealtypen influenced by changing scientific methods of thought? What is a harmonious urban region? Is this an urban Idealtype to be striven for in the current society with the actual fundamental trends?
Keywords: 330